The role of cell death in the physiological and pathological processes of skeletal muscle - Xu, Hongyi; Gao, Zihui; Yao, Xinlei; Sun, Jiacheng; Chen, Bingqian (Frontiers in Physiology, 2025)
Skeletal muscle is the largest metabolic and motor organ in the human body. It facilitates daily movement and maintains posture through contraction. It also acts as a core tissue for energy metabolism by participating in glucose uptake, lipid oxidation, and thermogenesis. Thus, it plays a vital role in regulating systemic metabolic homeostasis. Under physiological conditions, skeletal muscle maintains a dynamic regulatory network to coordinate multiple cellular processes for tissue homeostasis. Apoptosis selectively removes damaged myonuclei and maintains myofiber structural integrity. Necroptosis prevents excessive inflammatory responses. Autophagy degrades abnormal proteins and organelles to ensure cytoplasmic quality control. Additionally, pyroptosis supports immune surveillance. In pathological states, abnormal activation of cell death programs occurs. These include apoptosis, necrosis, autophagy, pyroptosis, and ferroptosis. Such dysregulation can lead to myonuclear loss, myofiber atrophy, and fibrosis. While previous reviews have often focused on individual cell death pathways, this review provides a novel, integrated perspective by systematically outlining the roles and regulatory mechanisms of multiple death modalities in skeletal muscle. The interactions and balances among these pathways collectively determine muscle fate. We further discuss the implications of this network across various pathological contexts, such as muscular dystrophy, sarcopenia, and sepsis-induced atrophy. Finally, we identify promising therapeutic targets arising from this integrated view and discuss the challenges and future directions for translating these findings into clinical strategies. This review provides a comprehensive theoretical foundation for understanding the pathogenesis and treatment of skeletal muscle-related diseases.